Coping with Change: International Differences in the Returns to Skills - Eric A. Hanushek; Guido Schwerdt; Simon Wiederhold; Ludger Woessmann (Center for Economic Studies and ifo Institute (CESifo), 2016)
Expanded international data from the PIAAC survey of adult skills allow us to analyze potentialsources of the cross-country variation of comparably estimated labor-market returns to skills in amore diverse set of 32 countries. Returns to skills are systematically larger in countries that havegrown faster in the recent past, consistent with models where skills are particularly important foradaptation to dynamic economic change.
Keywords: J31; I20; O15; 330; cognitive skills; returns to education; economic growth; international comparisons